Suppression of a Novel Vitellogenesis-Inhibiting Hormone Significantly Increases Ovarian Vitellogenesis in the Black Tiger Shrimp, Penaeus monodon - Laphyai, Phaivit; Kruangkum, Thanapong; Chotwiwatthanakun, Charoonroj; Semchuchot, Wanita; Thaijongrak, Prawporn; Sobhon, Prasert; Tsai, Pei-San; Vanichviriyakit, Rapeepun (Frontiers in Endocrinology, 2021)
In this study, a novel Crustacean Hyperglycemic Hormone-type II gene (CHH-type II) was identified and biologically characterized in a shrimp, Penaeus monodon. Based on its structure and function, this gene was named P. monodon vitellogenesis-inhibiting hormone (PemVIH). The complete cDNA sequence of PemVIH consisted of 1,022 nt with an open reading frame (ORF) of 339 nt encoding a polypeptide of 112 amino acids. It was classified as a member of the CHH-type II family based on conserved cysteine residues, a characteristically positioned glycine residue, and the absence of CHH precursor-related peptide (CPRP) domain. The deduced mature PemVIH shared the highest sequence similarities with giant river prawn sinus gland peptide A. Unlike P. monodon gonad-inhibiting hormone (PemGIH), PemVIH was expressed only in the brain and ventral nerve cord, but not the eyestalks. Whole-mount immunofluorescence using a newly generated PemVIH antiserum detected positive signals in neuronal cluster 9/11 and 17 of the brain, commissural ganglion (CoG), and neuronal clusters of ventral nerve cord. The presence of PemVIH-positive neurons in CoG, a part of stomatogastric nervous system, suggested a potential mechanism for crosstalk between nutritional and reproductive signaling. The role of PemVIH in vitellogenesis was evaluated using RNA interference technique. Temporal knockdown of PemVIH in female subadults resulted in a 3-fold increase in ovarian vitellogenin expression, suggesting an inhibitory role of PemVIH in vitellogenesis. This study provided novel insight into the control of vitellogenesis and additional strategies for improving ovarian maturation in P. monodon without the current harmful practice of eyestalk ablation.